Cardiovascular problems in emergency medicine : a discussion-based review - Grossman, Shamai A.; Rosen, Peter L.; Wiley InterScience (Online service) (Chichester, West Sussex : John Wiley & Sons, 2011)
"This is a unique book in emergency medicine providing real discussions on emergency cardiac cases by world famous emergency physicians. Each chapter starts with a case and conversation between the authors on how to diagnose and manage the patient. The case discussion is followed by comprehensive information on diagnosis and management of the condition, providing the wider context, backed up with references, making the book a stand alone text of cardiac emergencies. Authored by experts in the field, this essential guide provides emergency physicians, nurses, EMTs and residents with a handy reference containing recommendations for managing cardiac emergency care. What makes the book unusual is that the chapters are unlike any other EM book written. Essentially this is an opportunity for the reader to learn from the discussions amongst the experts This is the first volume in a projected series Current Topics in Emergency Medicine edited by Peter Rosen and Shamai Grossman. The discussion-based format will be used for each book in the series"--Provided by publisher.
Front Matter -- Section One: Cardiac Ischemia. Chest Pain / Michael Bohrn, Amal Mattu, Brian Browne -- Non-ST-Segment Elevations Myocardial Infarction / David Plitt, William J Brady -- ST-Segment Elevation Myocardial Infarction / David F M Brown -- Unusual Causes of Myocardial Ischemia / Robin Naples, Richard Harrigan -- Section Two: Cardiac Dysrhythmias. Bradyarrhythmias / Colleen Birmingham, Edward Ullman -- Atrial Fibrillation / Kristen Cochran, Shamai Grossman -- Supraventricular Tachycardia / Theodore Chan -- The Differential Diagnosis of Wide Complex Tachycardia--ED Diagnostic and Management Considerations / Nathan Charlton, William J Brady -- Cardiac Arrest / Benjamin J Lawner, Amal Mattu -- Strategies in out-of-Hospital Cardiac Arrest: Automatic External Defibrillator and Cardiopulmonary Resuscitation / Catherine Cleaveland, William J Brady -- Pacemakers and AICDS in Emergency Medicine / Theodore Chan -- Section Three: Non Ischemic Cardiac Disease. Acute Heart Failure / Kevin Reed, Amal Mattu -- Syncope / Shamai Grossman -- Valvular Heart Disease / Jeffrey Soderman, Edward Ullman -- Myocarditis / Jehangir Meer, Amal Mattu -- Pericarditis / Theodore Chan -- Cardiac Toxins and Drug-Induced Heart Disease / Jeffrey Green, Richard Harrigan -- Cardiomyopathy / Alden Landry, Shamai Grossman -- Section Four: Vascular Emergencies. Aortic Dissection / Keith A Marill, David F M Brown -- Abdominal Aortic Aneurysms / David A Peak, David F M Brown -- Hypertensive Emergencies / Russell Berger, Edward Ullman -- Section Five: Cardiac Testing. The Electrocardiogram in Acute Coronary Syndromes / Laura Oh, William J Brady -- Cardiac Markers / J Stephen Bohan -- Stress Testing / Jefferson G Williams, Shamai A Grossman -- Coronary Computed Tomography / J Tobias Nagurney, David F M Brown -- Section Six: Cardiac Surgery Complications. Postcardiac Surgery Emergencies / Jonathan Anderson, Shamai A Grossman -- Pediatric Cardiac Emergencies / Shannon Straszewski, Carrie Tibbles -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Cardiovascular emergencies -- Case studies; Evidence-based medicine -- Case studies; MEDICAL -- Cardiology; Cardiovascular emergencies; Evidence-based medicine; Cardiovascular Diseases; Emergency Treatment; Critical Care; Emergency Medical Services; Evidence-Based Medicine; Electronic books; Case studies; Case Reports